MENINGKATKAN MUTU TAMAN KANAK-KANAK RAJA DENGAN MENYUSUN RENCANA PENGEMBANGAN SEKOLAH MELALUI WORKSHOP DAN PEMBIMBINGAN - ., Yusnidar (Edu Research, 2017)
Each school led by good management all takes action, planning, implementation, evaluation, follow-up and school development. Research based on the objectives to be achieved, in order to work together to achieve common goals using workshops and mentorship. This research uses action research for three rounds. Each round consists of four stages: design, activity and observation, reflection and revision. The target of this research is the quality of TK Raja in Pematang Tebih Ujung Batu. The data obtained are the result of filling the instrument of quality improvement of TK Raja to school including Principal, Teacher and Student. The results showed that workshops and school development counseling had a positive effect on the quality and performance of TK Raja Pematang Tebih Ujung Batu. It can be said that this workshop and guidance can be used as an alternative effort to move School organization to improve school quality.